High order harmonic generation from SF6: Deconvolution of macroscopic effects - Wilson, B. P.; Fulfer, K. D.; Mondal, S.; Ren, X.; Tross, J.; Poliakoff, E. D.; Jose, J.; Le, Anh-Thu; Lucchese, R. R.; Trallero-Herrero, C. (My University, 2016)
We measure high order harmonics from the molecule SF6 over a large range of phase matching conditions and observe several features in the harmonics that are largely independent of such macroscopic conditions. The experimental data are then compared to the quantitative rescattering theory for the generation of harmonics from three orbitals. With this comparison, we are able to assign spectroscopic features in the harmonics to contributions from 1t1g (HOMO) and 5t1u (HOMO-1) orbitals.